Healing Brazil's Blue Amazon: The Role of Knowledge Networks in Nurturing Cross-Scale Transformations at the Frontlines of Ocean Sustainability - Gerhardinger, Leopoldo C.; Gorris, Philipp; Gonçalves, Leandra R.; Herbst, Dannieli F.; Vila-Nova, Daniele A.; De Carvalho, Fabiano G.; Glaser, Marion; Zondervan, Ruben; Glavovic, Bruce C. (Frontiers in Marine Science, 2018)
This paper dedicates to understanding of what is needed to achieve the transformation of ocean governance. Based on the theory of transformative agency conceptualized in a multi-level governance context, we build on recent novel inter- and transdisciplinary research in Brazil to explore the opportunities for transformation in the dynamic, complex and multi-level field of ocean governance. We focus this analysis on three transformation processes towards developing a socially and ecologically coherent marine protected area network as the core of a marine spatial planning process for enhanced ecosystem-based polycentric governance of the country’s Exclusive Economic Zone. The findings illuminate leverage points for achieving (much needed) transformation in Brazilian ocean governance and potentially beyond. These include: connecting transformative actions into coherent narratives and testing strategic advice derived from theories of transformative agency to promote regime shifts in ocean governance systems; setting of more ambitious social mobilization targets; fostering orchestration of knowledge-networks considering multiple issues, territorial and institutional levels; implementing institutional learning experiments; supporting transformational trajectories towards co-evolutionary, polycentric, ecosystem- and area-based ocean governance systems; and pursuing gradual, incremental structural understanding of a given knowledge network field as a major driver of catalysing transformative change. Hereby, this article advances understanding of how to better navigate the transformation towards enhanced sustainability in an important part of the Atlantic and hence of our global ocean.